PERUBAHAN KARAKTERISTIK TANAH DAN PENAMPILAN BEBERAPA VARIETAS PADI GOGO PADA KAWASAN PESISIR DENGAN PENAMBAHAN PUPUK HAYATI DAN BIOKOMPOS - Yudhi Harini Bertham; Abimanyu Dipo Nusantara; Bambang Gonggo Murcitro; Zainal Arifin (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2020)
[CHANGE IN SOIL CHARATERISTICS AND PERFORMANCE OF UPLAND RICE VARIETIES IN COASTAL AREA AS AMENDED WITH BIOFERTILIZER AND BIOCOMPOST]. Dryland in the coastal area has good potential for the cultivation of upland rice to reach food self-sufficiency and the development of future agriculture. Low fertility of the land the area can be overcome by using appropriate technology such as the use of superior varieties, bio-fertilizers, and bio compost. This study aimeds to (1) determine chemical and biological properties of coastal land to improve the growth of upland rice (2) find out the growth of upland rice in the coastal area using low input technology and (3) obtain upland rice varieties with high adaptability to a coastal area environment. The experimental design used was a split-plot design with the main plot of 3 upland rice varieties, namely Inpago 10, Serantan, and Local Variety, while the subplots are were fertilizer inputs namely [double inoculant P solubilized microbial p (pf) + K solubilized microbially + N fixation microbial N], [double inoculant P solubilized microbial (fma) + K solubilized microbially + N fixation micarobia], [biocompost at a dose of 10 tons/ha], and [inorganic fertilizer recommended by BPTP ie 200 kg Urea/ha, 100 kg SP36/ha, 100 kg KCl/ha]. The results showed that the coastal area has the potential for the development of upland rice cultivation. Also, the double inoculants of biological fertilizers were able to increase plant nutrient uptake, soil biological characteristics, and the growth of upland rice as compared to controls. Specifically, the best treatment is produced by application of [double inoculant microbial solvent p (pf) + microbial solvent K + microbial N fixation] combined with upland rice Inpago variety 10.